Repositioning Gratification as an Ordinary Criminal Offense in Indonesia’s Criminal Law System: a Conceptual Analysis and Directions for Legal Reform - Alendra, Alendra; Irawan, Agus; Pebrianto, Iin; Bustari, Hendra; Adrian, Salman (Jurnal Ilmu Hukum Kyadiren, 2026)
Gratification under the Indonesian Anti-Corruption Law (Undang-Undang Pemberantasan Tindak Pidana Korupsi) is classified as a special criminal offense characterized by a repressive approach, a broad legal definition, and the application of a reverse burden of proof. This regulatory framework raises normative concerns following the enactment of the 2023 National Criminal Code (Kitab Undang-Undang Hukum Pidana), which emphasizes the principles of legality, culpability, and proportionality in sentencing. This study aims to examine the legal construction of gratification, identify regulatory disharmony between the Anti-Corruption Law and the National Criminal Code, and assess the urgency of reformulating the legal status of gratification within the Indonesian criminal law system. Employing a normative juridical method with statutory, conceptual, and comparative approaches, the study finds a paradigmatic divergence and a heightened risk of overcriminalization resulting from the absence of a clearly defined mens rea element. The study concludes that reclassifying gratification as an ordinary criminal offense with differentiated sanctions is necessary to achieve a just, consistent, and effective criminal justice system.